PEMBERDAYAAN KADER “RAPID” DALAM UPAYA MENINGKATKAN DERAJAT KESEHATAN REMAJA DI KELURAHAN WONOKROMO SURABAYA - Chilyatiz Zahroh; Nurul Kamariyah; Siti Nurjanah (Community Development Journal, 2019)
This community service activities performed to optimize community involvement on a Kader of "RAPID" in an effort to increase degree movies teen health, these efforts are also expected to be formed to improve adolescent health cadres pengeta Huan, do mentoring on cadre health associated with adolescent teens that will eventually bring down juvenile delinquency numbers. The time of implementation of activities with a period of 3 months (from February to may 2018). Each RT is represented by two teenage cadre. Data collection with FGD (Focus Group Discussion) with Kader. FGD was attended by 16 Kader. The problem of the teens in the Neighborhood Wonokromo are drug use, free sex, and pregnant outside of marriage. The data recorded in full is the problem of pregnant outside of marriage which lead to dropping out of school for young women. Efforts are being made, with cadres is the detection of the number of teenagers, accurate information about the teenagers who become pregnant outside of marriage, and supply about the dangers of drugs. Unusa with Kader perform the handling and prevention of juvenile delinquency, in an attempt to increase the degree of the health of adolescents. Teens are the next generation, and our responsibility to fix the juvenile delinquency in the environment around us. The results of the external activities of the community this is a report which has been published in journals and an increased knowledge of cadres. Keywords: Rapid Kader, teenagers, health